Development and causality Neo-Piagetian perspectives - Young, Gerald 1947-; SpringerLink (Online service). (New York Springer, 2011)
Development and Causality Neo-Piagetian Perspectives Gerald Young Over the years, Jean Piaget's revolutionary study of infant and child development has inspired much discussion and debate, evolving through the work of his followers and critics. Development and Causality continues in this tradition, bringing new depth to the theoretical base, integrating Piagetian and Freudian/Eriksonian models as well as presenting far-reaching original theory. This comprehensive synthesis of the field concentrates on core areas such as language acquisition, self development, social cognition, personality development, attachment, narrative development, and emotional development, and is written so readers at both basic and advanced levels of familiarity may benefit. Dozens of tables, graphs, and other visual materials aid readers in comprehension; and the book:   Reviews Piaget's original model as the starting point for current theory. Introduces the author's 25-step model of LIFESPAN cognitive development, and compares IT TO Case's and Fischer's models of cognitive socio-affective correspondence. Extends current theory in terms of self development, cognitive perception/misperception of the other, self-regulation, theory of mind, and multiple intelligences. Focuses in detail on socio-affective development: personality, emotions, attachment. Examines causality mechanisms in depth, from hemispheric specialization to complex adaptive systems. Speculates on evolutionary forces underlying developmental stages. Development and Causality is a bedrock reference for researchers and students in child and developmental psychology, and lends itself to practical applications for clinicians.
Overview of the present work -- The Biopsychosocial Model and Bio-Personal-Social Models -- Piaget and Development -- The Present Cognitive-Affective Stage Model: I Cognition -- The Present Model: II Postformal Stage, Affective Parallels, Systems -- Substages in the Neo-Piagetian Models of Case, Fischer, and Young -- Parallels in Cognitive Substages and Socio-Affectivity in Case -- Parallels in Cognitive Substages and Socio-Affectivity in Fischer -- Case and Fischer on Language and the Brain -- Recent Case and Colleagues -- Further Fischer: Comprehensive Summary, Adult Development -- Recent Fischer: Emotional Development -- Self Development -- Cognitive (Mis)Perception of the Self and Other -- Social Cognition/Theory of Mind -- Self Definition and Relatedness/ Self-Regulation in Development -- Cognitive Socio-Affective Complexes and Multiple Intelligences.
Electronic reproduction.
Keywords: Child development; Child psychology; Child; Infant; Models, Psychological; Psychological theory; Electronic books